Carta de Roberto H.Todd a J. Ruiz Soler - Todd, Roberto H.; Ruiz Soler, J. (My University, 1934)
Acuso de recibo por la cantidad enviada para ayudar a la viuda e hijos de Manuel Angel Martínez Dávila
Keywords: Martínez Dávila, Manuel A.,1883-1934